(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article discusses the requirements for a postiche workshop, safety regulations, the work process of wigmakers, and the set of tools and equipment necessary for performing postiche (wig-making) work.